2022
DOI: 10.3390/foods11172614
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Characterization of Volatile Compounds in Smoke-Flavored Sea Bass (Lateolabrax maculatus) during Processing via HS-SPME-GC-MS and HS-GC-IMS

Abstract: The present study aimed to ascertain how the volatile compounds changed throughout various processing steps when producing a smoke-flavored sea bass (Lateolabrax maculatus). The volatile compounds in different production steps were characterized by headspace-solid phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) and headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS). A total of 85 compounds were identified, and 25 compounds that may be considered as potential key compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…GC-IMS is a nontargeted analytical method for the identification of volatile compounds using retention time and drift time( Feng et al, 2022 ) and has the characteristics of rapid detection, intuitive results and portability. The topography obtained from the GC-IMS analysis in this study is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GC-IMS is a nontargeted analytical method for the identification of volatile compounds using retention time and drift time( Feng et al, 2022 ) and has the characteristics of rapid detection, intuitive results and portability. The topography obtained from the GC-IMS analysis in this study is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The volatile compounds were extracted according to the method described in Hua Feng [35] with minor modifications. In brief, approximately 2 g minced fish, 4 mL saturated sodium chloride solution, and 5 μL 2, 4, 6-trimethylpyridine solution (Internal Standard) were added to the headspace bottle.…”
Section: Hs-spme Extractionmentioning
confidence: 99%
“…Referring to the processing method of Çakir and Ayvaz 21 and Belichovska et al, 22 the pre-treated fish fillets were soaked in a salt solution for 4 h, then dried in a hot-air drying oven (60 °C, 2 h) to reach 65.5 ± 5.5% of the original weight by dry weight, and immersed in a solution of smoke flavoring in water for 2 min with a fish-toflavoring solution proportion of 1:15 (w/v), and smoked fillets were kept at room temperature for 2 h to react between smoke components and fish flesh and heated in an oven (180 °C, 10 min). To determine the optimal process parameters, select salt concentration (1, 3, 5, 7, and 9%), smoke flavors concentration (2, 4, 6, 8, and 10%), cooking temperature (70, 90, 110, 130, and 150 °C), and cooking time (5,15,25,35, and 45 min) were four groups of single factors, and the process was optimized through orthogonal experiments (Table S1).…”
Section: Experimental Designmentioning
confidence: 99%
“…However, after a long period of smoking, the direct contact between fish and smoke poses potential hazards and safety issues. 5 Therefore, smoke flavors have been developed, and treating fish with smoke flavors can be a successful alternative to obtain a similar smoky effect to the traditional process. 6 Many researchers have optimized the ″smoke flavoring″ process to obtain the best sensory properties of smoked fish fillets, 7,8 but most of the studies have focused mainly on the sensory aspects, ignoring the shelf-life of the product and its quality, especially the high risk of microbial contamination during storage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation